Anti-synchronisation of non-identical fractional order hyperchaotic systems. (3rd December 2020) - Alomari, A.K.; Al-Jamal, Mohammad F.; Tahat, Nedal
This paper deals with the anti-synchronisation of fractional order hyperchaotic systems. In particular, we employ the active control method to achieve complete anti-synchronisation between fractional order Lorenz and Chen hyperchaotic systems. Based on stability theorems in the fractional calculus, analysis of stability is performed for the proposed method. Numerical simulations demonstrate the feasibility of the proposed algorithm.